PERRON-FROBENIUS THEORY AND GRAPH - Disha Stanggo, Pratiwi
Perron-Frobenius theory is nonnegative matrices basic theorem that discuss eigenvalue and eigenvector properties from a matrix based on irreducible properties. A graph ???? = (V;E) is a system consists of nite non-empty set V , and set E of unordered pairs fu; vg, u; v 2 V and u 6= v. Eigenvalue of ???? can be determined from adjacency matrices, is matrix with entry (0; 1) that represents vertices adjacency of ????. The purpose of this project is to investigate the properties of the greatest eigenvalue of a graph, specically strongly connected graph that relate with Perron-Frobenius theory, and to investigate the properties of the greatest eigenvalue of regular connected graph.